Karakteristik Inovasi Pendidikan dan Pembelajaran PAI : Penelitian - Ali Makki (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This paper discusses various innovations in Islamic Religious Education (PAI) education and learning. Educational innovation is the application of new ideas, methods, technologies, or approaches to update and improve the quality of learning processes and outcomes to make them more relevant, effective, and efficient in responding to the challenges of the times. Learning innovation is the renewal or development of new methods, strategies, media, and technologies in the teaching and learning process to increase effectiveness, efficiency, relevance, and student engagement, making it more interesting and appropriate to the needs of the times, such as the use of digital technology, project-based learning, or flipped classroom models. The goal is to create a more meaningful learning experience, motivate students, and equip them with relevant skills for the future. This research is part of the relevance of the characteristics of Islamic Religious Education (PAI) education and learning innovation in the theories of educational experts. The purpose of this research is to determine and explain the characteristics of educational innovation. The method used in this research is qualitative with the type of library research.